The Development and Validation of the Feedback in Learning Scale (FLS) - Jellicoe, Mark; Forsythe, Alex (Frontiers in Education, 2019)
Research attention has shifted from feedback delivery mechanisms to supporting learners to receive feedback well (Winstone et al., 2017a). Recognizing feedback and the action necessary to take the next steps are vital to self-regulated performance (Zimmerman, 2000; Panadero, 2017). Evaluative judgments supporting such mechanisms are vital forces that promote academic endeavor and lifelong learning (Ajjawi et al., 2018). Measuring such mechanisms is well-developed in occupational settings (Boudrias et al., 2014). Understanding how these relate to self-regulated learning gains in Higher Education (HE) is less well-understood (Forsythe and Jellicoe, 2018). Here we refined a measure of feedback integration from the occupational research domain (Boudrias et al., 2014) and investigate its application to HE. Two groups of psychology undergraduates endorsed perspectives associated with feedback. The measure examines characteristics associated with feedback including message valence, source credibility, interventions that provide challenge, feedback acceptance, awareness, motivational intentions, and the desire to make behavioral changes and undertake development activities following feedback. Of these suggested characteristics, exploratory factor analysis revealed that undergraduate learners endorsed credible source challenge, acceptance of feedback, awareness from feedback, motivational intentions and the desire to take behavioral changes and participate in development activities formed a single factor. The structure of the instrument and hypothesized paths between derived factors was confirmed using latent variable structural equation modeling. Both models achieved mostly good, and at least acceptable fit, endorsing the robustness of the measure in HE learners. These finding increase understanding of HE learner's relationship with feedback. Here, acceptance of feedback predicts the extent to which learners found the source of feedback credible. Credible source challenge in turn predicts awareness resulting from feedback. Subsequently, awareness predicts motivations to act. These promising results, whilst cross-sectional, also have implications for programmes. Further research employing this instrument is necessary to understand changes in learner attitudes in developing beneficial self-regulated skills that support both programmes of study and graduates in their careers.